2014
DOI: 10.24111/jrihh.v6i1.1222
|View full text |Cite
|
Sign up to set email alerts
|

PEMANFAATAN LIMBAH KULIT DURIAN (Durio zibethinus) DAN KULIT CEMPEDAK (Artocarpus integer) SEBAGAI EDIBLE FILM

Abstract: Durian (Durio zibethinus) and cempedak (Artocarpus integer) peels waste are not used by the society. The research aim is to extract pectin from durian and cempedak peels and to formulate the pectin into edible films for food packaging. The research stages were first pre-treatment of durian and cempedak peels, pectin extraction, pectin drying, and  pectin application as edible films with concentration of 0%, 5%, and 15%. Based on this research it was concluded that pectin can be extracted from durian and cemped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…A study found that pectin can be extracted from durian peel with a yield result of 27.97%. The extracted pectin 6 E3S Web of Conferences 483, 02006 (2024) ISST 2023 https://doi.org/10.1051/e3sconf/202448302006 can be formulated into edible films for food packaging [25]. Durian peel can be used as a source of cellulose to produce CMC, which is used as a stabilizer, thickener, and emulsifier in the food industry.…”
Section: Durian Peelsmentioning
confidence: 99%
“…A study found that pectin can be extracted from durian peel with a yield result of 27.97%. The extracted pectin 6 E3S Web of Conferences 483, 02006 (2024) ISST 2023 https://doi.org/10.1051/e3sconf/202448302006 can be formulated into edible films for food packaging [25]. Durian peel can be used as a source of cellulose to produce CMC, which is used as a stabilizer, thickener, and emulsifier in the food industry.…”
Section: Durian Peelsmentioning
confidence: 99%
“…A sharp knife was used to cut open the durian fruit and separate the arils from the rinds. The durian rind was thinly cut into pieces with a thickness of around 0.5 cm to aid in the drying process (21). The smaller durian rinds were then spread out on aluminium sheets and dried in a hot air oven (Memmert, D06836, Germany) at 60 °C for about 24 hours, or until a constant weight was attained.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Other product of composting was not observed yet. The other product may useful for pesticide, as stated by Kusumaningtyas et.al [7] and edible material for many purposed as stated by Amaliyah [11].…”
Section: Fig 1 Scheme Of Processing Durian Rind Decomposition In Micmentioning
confidence: 99%